A representação decimal fracionária de números reais: aspectos teóricos e históricos - Abreu, Lia Oliveira de (Universidade Federal de São Carlos, 2021)
In this work we carry out a study on the history and concepts of development of the decimal representation of real numbers, which probably started with works by Simon Stevin in La Theinde (The tenth) in 1585 (STEVIN, 1997), having been perfected by John Napier in his treatise on logarithms, Mirifici logarithmorum canonis description (1614). We describe briefly the historical progress of the development of the object of study, also approaching mathematical aspects about the representation of real, rational and irrational numbers.
Fractional decimal representation of real numbers: theoretical and historical aspects
Keywords: Frações decimais; História da matemática; Dízimas periódicas; Decimal fractions; History of mathematics; Repeating decimals; CIENCIAS EXATAS E DA TERRA::MATEMATICA